A Programmable New Algorithm to Represent e-Abacus Diagram vertically and Its Application in Industrial Products - Ammar Seddiq Mahmood (African Journal of Advanced Pure and Applied Sciences, 2023)
The question often revolves around the extent to which the fields of mathematics can be applied, and is it possible to benefit from them in our lives? We try to provide direct answers to some of them, while we are unable to provide answers to other areas. However, in this work we will present a new vision different from everything that was presented on the subject of the e-abacus diagram; by using a vertical reading which is not previously used for any partition instead of the horizontal, where the works of each Hann and Thomas, Mukai and recently Kirani; each separately, in finding mathematical relationships with cotton and industrial products inspired us to find a link more than Wonderful, it will be useful in increasing production or the possibility of presenting one or more models for design through this diagram.